Blood gas analyses and other components involved in the acid-base metabolism of rats infected by Trypanosoma evansi - Baldissera M.D. (2015)
© 2014.The aim of this study was to investigate the effects of Trypanosoma evansi infections on arterial blood gases of experimentally infected rats. Two groups with eight animals each were used; group A (uninfected) and group B (infected). Infected animals were daily monitored through blood smears that showed high parasitemia with 30 trypanosomes per field (1000×) on average, 5 days post-infection (PI). Arterial blood was collected at 5 days PI for blood gas analysis using an automated method based on dry-chemistry. Hydrogen potential (pH), partial oxygen pressure (pO2), oxygen saturation (sO2), sodium (Na), ionic calcium (Ca ionic), chlorides (Cl), partial dioxide carbon pressure (pCO2), base excess (BE), base excess in the extracellular fluid (BEecf), bicarbonate (cHCO3), potassium (K), lactate, and blood total dioxide the carbon (tCO2) were evaluated. The levels of pH, pCO2, BE, BEecf, cHCO3, and tCO2 were significantly decreased (P < 0.05) in group B compared to group A. Additionally, the same group showed increases in Cl and lactate levels when compared to uninfected group. Therefore, it is possible to state that the infection caused by T. evansi led to alterations in the acid-base status, findings that are correlated to metabolic acidosis.